Lower levels of insulin‐like growth factor‐1 standard deviation score are associated with histological severity of non‐alcoholic fatty liver disease. Issue 7 (30th September 2014) - Sumida, Yoshio; Yonei, Yoshikazu; Tanaka, Saiyu; Mori, Kojiroh; Kanemasa, Kazuyuki; Imai, Shunsuke; Taketani, Hiroyoshi; Hara, Tasuku; Seko, Yuya; Ishiba, Hiroshi; Okajima, Akira; Yamaguchi, Kanji; et al.
<x xml:space="preserve">Abstract</x> Aim Growth hormone (GH) deficiency may be associated with histological progression of non‐alcoholic fatty liver disease (NAFLD) which includes non‐alcoholic fatty liver (NAFL) and non‐alcoholic steatohepatitis (NASH). Insulin‐like growth factor 1 (IGF‐1) is mainly produced by hepatocytes and its secretion is stimulated by GH. Our aim was to determine whether more histologically advanced NAFLD is associated with low circulating levels of IGF‐1 in Japanese patients. Methods Serum samples were obtained in 199 Japanese patients with biopsy‐proven NAFLD and in 2911 sex‐ and age‐matched healthy people undergoing health checkups. The serum levels of IGF‐1 were measured using a commercially available immunoradiometric assay. The standard deviation scores (SDS) of IGF‐1 according to age and sex were also calculated in NAFLD patients. Results The serum IGF‐1 levels in NAFLD patients were significantly lower (median, 112 ng/mL) compared with the control population (median, 121 ng/mL, P < 0.0001). IGF‐1 SDS less than −2.0 SD from median were found in 11.6% of 199 patients. NASH patients exhibited significantly lower levels of IGF‐1 SDS (n = 130; median, −0.7) compared with NAFL patients (n = 69; median, −0.3; P = 0.026). The IGF‐1 SDS values decreased significantly with increasing lobular inflammation (P < 0.001) and fibrosis (P < 0.001). In multiple regressions, the association between the IGF‐1 SDS values and the severity of NAFLD persisted after adjusting for age, sex and insulin resistance. Conclusion Low levels of circulating IGF‐1 may have a role in the development of advanced NAFLD, independent of insulin resistance. Supplementation with GH/IGF‐1 may be a candidate for the treatment of NASH.